Meat yield characteristics and physicochemical properties of different duck genotypes - Sarker, MSH; Habib, M; Bhuiyan, MSA; Hashem, MA; Ali, MS (Meat Research, 2022)
This work was conducted to investigate the meat yield characteristics and physicochemical properties of Pekin (P), Nageswari (N) and two reciprocal F1 crossbred P♂× N♀ and N♂× P♀. For this purpose 16 ducks (8 male and 8 female) of 4 duck genotypes were randomly selected from Animal Breeding and Genetics farm of BAU at their average weight. The average live weights of P, N, P♂ × N♀ and N♂ × P♀ genotypes at 12th week of age were 2370.00±70g, 1823.33±154.52g, 1896.67±105.25g and 1823.33±14.53g respectively. In case of live weight, Pekin duck showed significantly higher body weight compare to other genotype. However, no significantly difference were found in Nageswari and their crosses (p<0.05). Dressing (%) in Pekin, Nageswari, and the F1 crossbreds P♂× N♀, N♂×P♀ were 68.81±1.05, 69.01±1.38, 71.13±1.20 and 69.11±0.55%, respectively with no significant difference in dressing percentage among the genotypes. Similarly, breast weight, leg weight, shank weight, head weight, wing weight, liver weights and gizzard weight did not show significant differences among the four genotypes. The pH level of four genotypes at 15 minute, 1 hour, 6 hour and 24 hour of post-mortem was observed for breast and leg meat. No significant differences were found in pH level of breast and leg meat at different post-mortem time. Cooking loss and drip loss of breast and leg meat also showed similar results with no significant differences among the genotypes. Proximate composition of breast and leg meat also did not show significant differences among the genotypes. In conclusion, the present result shows that genotype had no role in variation of duck meat.